Enhanced protection against malaria by indoor residual spraying in addition to insecticide treated nets: is it dependent on transmission intensity or net usage? - Philippa A West; Natacha Protopopoff; Alexandra Wright; Zuhura Kivaju; Robinson Tigererwa; Franklin W Mosha; William Kisinza; Mark Rowland; Immo Kleinschmidt (PLoS ONE)
Background Insecticide treated nets (ITNs) and indoor residual spraying (IRS) are effective vector control tools that protect against malaria. There is conflicting evidence regarding whether using ITNs and IRS in combination provides additional benefit over using either of these methods alone. This study investigated factors that may modify the effect of the combined use of IRS and ITNs compared to using ITNs alone on malaria infection prevalence. Methods Secondary analysis was carried out on data from a cluster randomised trial in north-west Tanzania. 50 clusters received ITNs from a universal coverage campaign; of these 25 were randomly allocated to additionally receive two rounds of IRS in 2012. In cross-sectional household surveys children 0.5-14 years old were tested for Plasmodium falciparum infections (PfPR) two, six and ten months after the first IRS round. Results IRS protected those sleeping under nets (OR = 0.38, 95%CI 0.26-0.57) and those who did not (OR = 0.43, 95%CI 0.29-0.63). The protective effect of IRS was not modified by community level ITN use (ITN use<50%, OR = 0.39, 95%CI 0.26-0.59; ITN use> = 50%, OR = 0.46, 95%CI 0.28-0.74). The additional protection from IRS was similar in low (<10% PfPR, OR = 0.38, 95%CI 0.19-0.75) and high transmission areas (≥10% PfPR, OR = 0.34, 95%CI 0.18-0.67). ITN use was protective at the individual-level regardless of whether the village had been sprayed (OR = 0.83, 95%CI 0.70-0.98). Living in a sprayed village was protective regardless of whether the individual slept under an ITN last night (OR = 0.41, 95%CI 0.29-0.58). Interpretation Implementing IRS in addition to ITNs was beneficial for individuals from villages with a wide range of transmission intensities and net utilisation levels. Net users received additional protection from IRS. ITNs were providing some individual protection, even in this area with high levels of pyrethroid insecticide resistance. These results demonstrate that there is a supplementary benefit of IRS even when ITNs are effective. Trial registration ClinicalTrials.gov NCT01697852.